Sustainability transformation: The impact of GHRM and sustainable dynamic capability on sustainable business performance - Retno Purwani Setyaningrum; Tri Ngudi Wiyatno; Erina Rulianti (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
This study aims to examine the influence of Green Human Resource Management (GHRM) and sustainable dynamic capability on sustainable business performance, while analyzing the moderating role of organizational inertia. A quantitative research design was applied, using survey data collected from 120 manufacturing companies in West Java, Indonesia. Data analysis was conducted using SEM-PLS to test the hypothesized relationships among variables. The results indicate that both GHRM and sustainable dynamic capability significantly and positively affect sustainable business performance. Moreover, organizational inertia was found to moderate the relationship between GHRM and sustainable business performance, where higher levels of inertia weaken the positive effect of GHRM on business sustainability outcomes. This study is limited to manufacturing companies located in West Java, Indonesia, which may affect the generalizability of the findings to other regions or industries. Future research could broaden the scope by including different sectors and geographic areas to validate and extend these results. Additionally, longitudinal studies are recommended to observe the dynamic effects of GHRM and sustainability capabilities over time. This study offers novel insights into the interaction between GHRM, sustainable dynamic capability, and organizational inertia in achieving sustainable business performance, contributing to both sustainability and HRM literature.